Toxicity, Antioxidant and Antibacterial Test of Ethyl Acetate Extract of Jamblang Leaves (Syzygium cumini L.) - Zultira Harina Roza; Lenni Fitri; Amalia (Postgraduate, University of Mataram, 2026)
Jamblang (Syzygium cumini L.) is a plant from the Myrtaceae family that is used as a traditional medicine, especially its leaves. This study aims to determine the toxicity, antioxidant, and antibacterial activities of the ethyl acetate extract of jamblang leaves and to identify its secondary metabolite compounds. The toxicity test using the Brine Shrimp Lethality Test (BSLT) method showed that the ethyl acetate extract of jamblang leaves had an LC₅₀ value of 174.602 ppm, which falls into the toxic category. The antioxidant test using the DPPH method showed an IC₅₀ value of 4.268 µg/mL, which is classified as strong, although still weaker than vitamin C (IC₅₀ = 2.437 µg/mL). The antibacterial test against Streptococcus mutans using the disc diffusion method produced inhibition zones of 2.58 mm (20%), 6.61 mm (30%), and 9.08 mm (40%), with a Minimum Inhibitory Concentration (MIC) value of 25%. Identification of secondary metabolites using GC-MS revealed 38 compounds belonging to terpenoid, ester and aromatic Hyhrocarbons groups. These results indicate that the ethyl acetate extract of jamblang leaves possesses toxicity, antioxidant, and antibacterial properties, thus having the potential to be developed as a phytopharmaceutical.